... euro area report (Publications Office of the European Union, 2023)
After a continued rebound in 2022, the euro-area economy witnessed a strong deceleration this year. In 2022, the growth boost resulting from the post-COVID reopening of the economy, together with policy support, led to a solid 3.4% economic expansion. Despite the rapid rise in energy prices in the winter of 2022, the euro area avoided a recession. The robust labour market has been and remains a key element of macroeconomic resilience and supportive of aggregate demand. Still, high consumer prices and tightening financing conditions have resulted in a loss of growth momentum over the course of 2023. For 2023, GDP for the euro area is expected to grow by 0.6%, with some Member States recording negative growth for the year as a whole.
10.2765/049223
Keywords: Graue Literatur; euro area; macroeconomics; inflation; price of energy; monetary policy; labour market; financial risk; fiscal policy; euro; Economic and Monetary Union; financial stability; competitiveness; activity report